2012
DOI: 10.1007/s00423-012-0915-y
|View full text |Cite
|
Sign up to set email alerts
|

Immune mediators of postoperative ileus

Abstract: The present manuscript will give an update on the inflammatory responses, the involved cell types, and participating immune mediators in POI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 79 publications
4
53
0
2
Order By: Relevance
“…Substantial experimental studies demonstrated that POI severity was correlated with levels of inflammatory cytokines such as TNF-α, IL-1, and IL-6, and the activation level of inflammatory cells (e.g. macrophages, mast cells) [27,28,29,30,31,32,33,34]. A pilot study from The et al [35] revealed promising results in the prevention of POI with mast cell stabilization treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial experimental studies demonstrated that POI severity was correlated with levels of inflammatory cytokines such as TNF-α, IL-1, and IL-6, and the activation level of inflammatory cells (e.g. macrophages, mast cells) [27,28,29,30,31,32,33,34]. A pilot study from The et al [35] revealed promising results in the prevention of POI with mast cell stabilization treatment.…”
Section: Discussionmentioning
confidence: 99%
“…27,37,38) These cytokines act as inhibitors and contribute to the gastrointestinal dysmotility through their direct cytotoxic action or their effect on the production of nitric oxide and prostanoids. 24) In contrast to these pro-inflammatory cytokines, anti-inflammatory cytokine IL-10 actively down-regulates intestinal inflammatory process to prevent an excessive and prolonged inflammation. 24) In addition, it is reported that IL-10 deficiency could lead to a prolonged gastrointestinal dysmotility after surgery and abnormal high gene expression of pro-inflammatory cytokines in the animal model of POI.…”
Section: Discussionmentioning
confidence: 99%
“…24) In contrast to these pro-inflammatory cytokines, anti-inflammatory cytokine IL-10 actively down-regulates intestinal inflammatory process to prevent an excessive and prolonged inflammation. 24) In addition, it is reported that IL-10 deficiency could lead to a prolonged gastrointestinal dysmotility after surgery and abnormal high gene expression of pro-inflammatory cytokines in the animal model of POI. 39) In the present study, we found that POI rats showed significantly higher levels of pro-inflammatory cytokine TNF-α, IL-1β and IL-6 in serum and the ileum tissue, while these elevated levels were significantly reduced by GRb1 in a dose-dependent manner, as well as their gene expression in the ileum tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How, for instance, might genetic and molecular characteristics of cancer cells be exploited for the prevention of pancreatic cancer [3], to bypass the resistance of colorectal tumours against chemoand radiation therapy [4], or to develop suitable biomarkers for oncologic treatment [5]? What are immune mechanisms underlying postoperative intestinal dysmotility-and how can they be influenced to devise innovative strategies for the treatment of postoperative ileus [6]? How do alterations in hepatic blood flow impact on liver regeneration and, thus, on clinical outcomes following surgical liver resection [7]?…”
mentioning
confidence: 99%